Placebo and nocebo effects of percutaneous needle electrolysis and dry-needling: an intra and inter-treatment sessions analysis of a three-arm randomized double-blinded controlled trial in patients with patellar tendinopathy - Doménech-García, Víctor; Pecos-Martín, Daniel; Blasco-Abadía, Julia; Bellosta-López, Pablo; López-Royo, María Pilar (Frontiers in Medicine, 2024)
Objective This study aimed to investigate the influence of potential placebo and nocebo effects on pain perception of percutaneous needle electrolysis (PNE) in individuals with patellar tendinopathy. Methods In this secondary analysis of a three-arm randomized double-blinded controlled trial, intra and inter-session pain perception data from 48 sporting participants with patellar tendinopathy between 18 and 45 years were investigated. Participants were divided into 3 parallel groups: “no-sham group” [PNE intervention], “single-sham group” [sham PNE by using dry needling], and “double-sham group” [sham PNE by using sham needles]. Every group received 4 sessions of the needling therapies targeting the patellar tendon over 8 weeks and was instructed to perform a unilateral eccentric exercise program of the quadriceps muscle on the affected side. Clinical and needle-related pain was assessed before, during, and after each treatment session using a visual analog scale. Results No differences were found between groups intra- or inter-session in terms of pain reduction (P = 0.424) despite clinical pain decreased in all groups since the first treatment session (P < 0.001). Furthermore, although the double-sham group showed a lower percentage of participants reporting needle-related pain during needle intervention (P = 0.005), the needle-related pain intensity after needle intervention was similar between groups (P = 0.682). Moreover, there were no group differences for the duration of pain sensation after any needle intervention (P = 0.184), extending in many cases beyond 24 h. Conclusion Needling therapies for individuals with patellar tendinopathy are prone to elicit placebo effects regarding clinical pain and nocebo effects regarding needling-related pain. Clinicians and physical therapists treating musculoskeletal pain conditions should consider the added value and potential mechanisms of action before routinely using needle techniques.